2016
DOI: 10.1002/chem.201601706
|View full text |Cite
|
Sign up to set email alerts
|

On the Nature of Bridging Metal Atoms in Intermetalloid Clusters: Synthesis and Structure of the Metal‐Atom‐Bridged Zintl Clusters [Sn(Ge9)2]4− and [Zn(Ge9)2)]6−

Abstract: The addition of Sn and Zn ions to [Ge ] clusters by reaction of [Ge ] with SnPh Cl , ZnCp* (Cp*=pentamethylcyclopentadienyl), or Zn [HC(Ph P=NPh) ] is reported. The resulting Sn- and Zn-bridged clusters [(Ge )M(Ge )] (M=Sn, q=4; M=Zn, q=6) display various coordination modes. The M atoms that coordinate to the open square of a C -symmetric [Ge ] cluster form strong covalent multicenter M-Ge bonds, in contrast to the M atoms coordinating to triangular cluster faces. Molecular orbital analyses show that the M ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 89 publications
1
28
0
2
Order By: Relevance
“…Recently, the unique synthetic peculiarities of N‐heterocyclic carbenes (NHC) have been applied to tetrel Zintl clusters, as coinage metal NHC complexes were reacted with [Ge 9 {Si(SiMe 3 ) 3 } 3 ] – . From these reactions resulted the neutral cluster compounds [(dipp) M (η 3 ‐Ge 9 (Si(SiMe 3 ) 3 ) 3 )] [dipp = 1,3‐bis(2,6‐diisopropylphenyl)imidazol‐2‐ylidene, M = Cu, Ag, Au] and the low‐charged [Ag(Ge 9 {Si(SiMe 3 ) 3 } 3 ) 2 ] – complex anion with a sandwich‐like shape, similarly known from bare [ E 9 ] clusters, which can be connected via main group or transition metal atoms . The [Ge 9 {Si(SiMe 3 ) 3 } 3 ] – clusters in the new coinage metal complexes, either neutral or sandwich‐like, are coordinated by a triangular Ge 3 face, indicating the persistence of the threefold cluster symmetry in the resulting products.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the unique synthetic peculiarities of N‐heterocyclic carbenes (NHC) have been applied to tetrel Zintl clusters, as coinage metal NHC complexes were reacted with [Ge 9 {Si(SiMe 3 ) 3 } 3 ] – . From these reactions resulted the neutral cluster compounds [(dipp) M (η 3 ‐Ge 9 (Si(SiMe 3 ) 3 ) 3 )] [dipp = 1,3‐bis(2,6‐diisopropylphenyl)imidazol‐2‐ylidene, M = Cu, Ag, Au] and the low‐charged [Ag(Ge 9 {Si(SiMe 3 ) 3 } 3 ) 2 ] – complex anion with a sandwich‐like shape, similarly known from bare [ E 9 ] clusters, which can be connected via main group or transition metal atoms . The [Ge 9 {Si(SiMe 3 ) 3 } 3 ] – clusters in the new coinage metal complexes, either neutral or sandwich‐like, are coordinated by a triangular Ge 3 face, indicating the persistence of the threefold cluster symmetry in the resulting products.…”
Section: Introductionmentioning
confidence: 99%
“…Metal‐linked macromolecular species based on [E 9 ] q− building blocks have also been obtained, as illustrated by clusters [{Ni(CO) 2 } 2 (u‐Si 9 ) 2 ] 8− , [(Ge 9 )Hg(Ge 9 )] 2− , [Hg 3 (Ge 9 ) 4 ] 10− , ∞[(μ 2 ‐Hg)(Ge 9 ) 2− ] . [(Ge 9 )Sn(Ge 9 )] 4− , [(Ge 9 )Zn(Ge 9 )] 6− , [(Ge 9 )In(Ge 9 )] 2− , [(Ge 9 Zn)‐(Ge 9 )‐(ZnGe 9 )] 8− , [Ag(Sn 9 ) 2 ] 6−[90] and [Au 3 Ge 45 ] 9− . In addition, it was found that in the [Ge 9 Zn‐ZnGe 9 ] 6−[89] and [Pb 9 Cd‐CdPb 9 ] 6−[92] clusters, the [E 9 ] q− fragments stabilize covalent Cd‐Cd and Zn‐Zn bonds, respectively.…”
Section: Spherical Aromaticity Of Homoatomic Polyhedra [En]q− (E=si mentioning
confidence: 99%
“…Thef irst examples of such an h 4 -coordination were observed by Haushalter and Eichhorn in [Sn 9 M(CO) 3 ] 4À and [Pb 9 M(CO) 3 ] 4À (M = Cr,Mo, W), [56] in which the open square of Tt 9 acts as a p-electron donor with similar electronic properties as Cp (cyclopentadienyl), Cp* (1,2,3,4,5-pentamethylcyclopentadienyl), or arene ligands.M eanwhile,t he ability of the Tt 9 unit to serve as al igand at transition-metal centers is well studied, and representatives of according coordination compounds are known for ab road variety of transition metals,i ncluding Zn and Cd. [57] Substitution of all ligands of the applied metal organyls results in clusters connected via bare metal atoms,such as in the dimers [Ge 9 M-Ge 9 ] 6À (M = Sn, Zn, Cu), [58] the oligomers [Zn 2 (Ge 9 ) 3 ] 8À [59] and [Hg 3 (Ge 9 ) 4 ] 10À , [60] or the polymeric species 1 1 ½ZnGe 9 ] 2À[59, 61] and 1 1 ½HgGe 9 ] 2À . [62] Even clusters bridged by am etal-metal bond as in [Ge 9 Zn-ZnGe 9 ] 6À or [Pb 9 Cd-CdPb 9 ] 6À are existent, either describable as as mall M 2 unit (M = Zn, Cd) bearing two nido cluster ligands or as acovalently linked dimer of two closo clusters (see also section 5).…”
Section: Tt 9 and M@tt 9 Cluster Precursorsmentioning
confidence: 99%